CAREER DIRECTION OF FUTURE TEACHERS IN THE CONTEXT OF MODERN CAREER ORIENTATION STRATEGIES - Mykhailichenko, Mykola; Pryhodii, Mykola (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The modern professional environment, which ensures the training of future teachers, is determined by such factors as satisfaction with the content and organization of pedagogical work; the nature of the relationship between the participants of the educational process; the presence of the necessary spatial and subject conditions that ensure the prestige of both the educational institution in particular and the teaching profession in general. Under such conditions, the opportunity to realize the student’s individual educational trajectory, reveal his creative potential, and ensure effective personal self-realization and professional self-development are achieved. The purpose of this article is to explore and substantiate effective career guidance strategies aimed at shaping future teachers’ professional identity and career orientation, considering the contemporary challenges of teacher education and labour market demands. The objectives include characterizing modern career guidance strategies and, using diagnostic methods, highlighting the role of the educational-professional environment as a tool for shaping the career orientation of future teachers. The research employs theoretical methods (study and analysis of theoretical sources, comparison of different approaches and methods) and practical methods (conducting surveys). The articles reveal the problem of professional orientation as a fundamental component of the training of future teachers, which forms a professional identity, directs their career trajectories, and ensures long-term success and satisfaction from work in the educational field. The current realities of a complex and dynamic educational environment reinforce the role of effective professional orientation, which helps future teachers make informed decisions about their career path and equips them with the necessary tools to overcome professional challenges. The article reveals the scientific approaches of leading foreign authors to various methods and strategies that help individuals determine their professional interests, abilities and goals. The work experience of the career guidance centre of the “Uman T.G. Shevchenko Humanitarian and Pedagogical Vocational College of the Cherkasy Regional Council”, in particular, the content, forms and methods of career orientation support for applicants, students and graduates of the institution, as well as the main career orientations of education seekers. It was concluded that current career guidance programs and tools help students better understand their professional interests and abilities.